“As filhas de São Francisco”: estratégias e experiências educativas da congregação das irmãs franciscanas de nossa senhora dos anjos em Bacabal/MA (1960-1980) - LEMOS, Jádson Rudson Rodrigues (2021)
This dissertation aimed to analyze the performance of the Congregation of the Franciscan Sisters of Nossa Senhora dos Anjos, focusing on the missionary educational project undertaken by them in Bacabal/MA, between the 1960s and 1980s. in the organization of the College of Nossa Senhora dos Anjos, founded by the nuns, highlighting aspects such as the physical structure, schedules, disciplines, contents, curriculum and organization of time (profane and sacred), formation of girls and women. The research methodology, of a documentary nature, took into account the approach of some researches on the performance of women's congregations that were specifically elaborated in the area of education in recent years, as well as the writings produced by the religious themselves. Regarding the College, the collated documentation consisted basically of the analysis of minutes, enrollment books and other official documents issued by the school. The reports and testimonies of religious were included with the aim of helping to understand the educational role played by the said Congregation. The theoretical assumptions that guided the foundations of the research were those related to the theme, especially BARROS, 2010; CUSTODY, 2015; LEONARDI, 2011; NERIS, 2014 and PEREIRA, 2011. This work allowed to historically reconstitute the work of the Congregation of the Franciscan Sisters of Our Lady of the Angels in Bacabal/MA. The research showed that the missionary-educational work undertaken by the Sisters reached a remarkable resonance and constituted one of the historical landmarks of the Congregation's performance in the region. In addition, the College played a key role in educating girls and women. The female education at CONASA, under the pedagogical organization of the sisters, indicated that there was an educational process divided into a solid moral and Christian formation. With regard to school practices, it is worth noting that the subjects offered, the pedagogical practices, the disseminated methods, aimed mainly at the evangelization of students. As a conclusion to the work, an online gallery was created, consisting of photographic, memorial and historical records that were housed on the Congregation's own website, with a focus on its use as research material and pedagogical resource in the classroom.